Manajemen Strategi dengan Pendekatan Analisis SWOT dalam Meningkatkan Kepuasan Pemustaka - Sri Wahyuni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The presence of the library has an important role in transferring knowledge to society in modern era. In the library, it was necessary to implement a good strategic management that aims to have a positive impact on improving the quality of library development. This study wants to analyze the strategic management carried out by the Tanah Datar District Public Library using SWOT analysis approach in increasing user satisfaction. The type of research used was qualitative research with a qualitative approach, here the researcher wants to examine more deeply related to the problems studied. The results showed that from the approach used through the SWOT Analysis got obtained for the library where in terms of the strength of the library where the strategic location is in the city center, but in terms of weaknesses seen in terms of collections that are still incomplete, in terms of opportunities, namely supported by regional revenue and expenditure budget funds. which was routine every year, while the challenge was the lack of staff competence in library technology. Furthermore, it was seen from the analysis of user satisfaction seen from the aspect of the service provided is maximal with a friendly and polite attitude, while in terms of the collection it is still incomplete. From these results, it was hoped that the library can increase the number of collections and conduct training for librarians to improve competence in the field of information and technology.